Manajemen Terapi Bakterial Meningitis Akut pada Pasien Anak (Fokus Terapi Antibiotik dan Kortikosteroid): Management of AcuteBacterial Meningitis Therapy in Pediatric Patients (Focus on Antibioticand Corticosteroid Therapy) - Pandu Laksono; Pande Made Ayu Aprianti; Patricia Valery Rahaded; Hidayati Adi Putri; Rizqiyanti Ramadhani; Jainuri Erik Pratama; Antonius Adji Prayitno Setiadi; Marisca Evalina Gondokesumo (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Acute bacterial meningitis is an inflammatory condition of the brain that develops rapidly due to bacterial infection in the lining of the brain (meninges) or in the subarachnoid space (fluid-filled space between the meninges). Common clinical manifestations include headache, fever, convulsions, and nuchal rigidity with diagnosis based on cerebrospinal fluid analysis. Management of cases of acute bacterial meningitis, especially in pediatric patients, focuses on selecting antibiotics and corticosteroids as the key treatment, followed by other supportive therapies such as antifever and anticonvulsants. There is a case of a 1-year-old child with a diagnosis of bacterial meningitis, this case report aims to examine the selection, dosage, method of administration, and monitoring of the effectiveness of antibiotics and corticosteroids as therapy in this case. The patient received treatment at RSUD Dr. Soetomo for 4 days by receiving ceftriaxone and dexamethasone injections per kg of body weight. In this case, observation was carried out in the form of observing the patient's clinical condition every day until the patient experienced an improvement in seizures and fever from the 2nd day of treatment. On the 4th day, the patient was allowed to go home and continue oral therapy for outpatient treatment. In conclusion, patients with acute bacterial meningitis need to be given antibiotics which must be started as soon as possible, aimed at eradicating bacteria that infect the lining of the brain, while corticosteroid injections are aimed at reducing the inflammatory response that occurs in the brain so as not to worsen the prognosis of the disease in my condition. Keywords: bacterial meningitis, ceftriaxone, dexamethasone Abstrak Meningitis bakterial akut adalah kondisi peradangan otak yang berkembang dengan cepat akibat infeksi bakteri pada selaput otak (meningen) atau pada ruang subarachnoid (ruang berisi cairan di antara meningen). Manifestasi klinis yang umum meliputi sakit kepala, demam, kejang dan kakukuduk dengan penegakan diagnosis berdasarkan analisis cairan serebrospinal. Penatalaksanaan kasus bakterial meningitis akut, khususnya pada pasien anak-anak difokuskan pada pemilihan antibiotik dan kortikostreroid sebagai kunci pengobatan, diikuti dengan terapi suportif lain seperti antidemam dan antikonvulsi. Terdapat kasus anak berusia 1 tahun dengan diagnosa bakterial meningitis, laporan kasus ini bertujuan untuk mengkaji pemilihan, dosis, cara pemberian serta monitoring efektivitas antibiotik dan kortikosteroid sebagai terapi pada kasus ini. Pasien mendapatkan perawatan di RSUD Dr. Soetomo selama 4 hari dengan mendapatkan injeksi ceftriaxone dan deksametason per kg berat badan. Pada kasus ini dilakukan pengamatan berupa observasi kondisi klinis pasien setiap harinya hingga pasien mengalami perbaikan kejang dan demam sejak hari ke-2 perawatan. Pada hari ke-4, pasien diperbolehkan pulang dengan melanjutkan terapi per oral untuk menjalani rawat jalan. Kesimpulannya, pasien dengan meningitis bakterial akut perlu pemberian antibiotik yang harus dimulai sesegera mungkin yang ditujukan untuk eradikasi bakteri penginfeksi selaput otak sedangkan pemberian injeksi kortikosteroid ditujukan untuk menurunkan respon inflamasi yang terjadi di otak agar tidak memperparah prognosis penyakit pada kondisi akut Kata Kunci: bakterial meningitis, ceftriaxone, deksametason